Particle Physics Reference Library : Volume 2: Detectors for Particles and Radiation - Fabjan, Christian W.; Schopper, Herwig; Fabjan, Christian W.; Schopper, Herwig (Springer Nature, 2020)
This second open access volume of the handbook series deals with detectors, large experimental facilities and data handling, both for accelerator and non-accelerator based experiments. It also covers applications in medicine and life sciences. A joint CERN-Springer initiative, the (3z(BParticle Physics Reference Library(3y (Bprovides revised and updated contributions based on previously published material in the well-known Landolt-Boernstein series on particle physics, accelerators and detectors (volumes 21A,B1,B2,C), which took stock of the field approximately one decade ago. Central to this new initiative is publication under full open access.s
English
Keywords: Particle & high-energy physics; Mensuration & systems of measurement; Quantum physics (quantum mechanics & quantum field theory); Atomic & molecular physics; Nuclear power & engineering; Particle Acceleration and Detection, Beam Physics; Measurement Science and Instrumentation; Elementary Particles, Quantum Field Theory; Nuclear Physics, Heavy Ions, Hadrons; Nuclear Energy; Accelerator Physics; Nuclear Physics; High-energy physics handbook; Standard model of particle physics; Fundamental particles and forces; Physics of particle detectors; Accelerators and beams; Open Access; Particle & high-energy physics; Scientific standards, measurement etc; Quantum physics (quantum mechanics & quantum field theory); Atomic & molecular physics; Nuclear power & engineering